Discovery and mechanism of intestinal bacteria in enzymatic cleavage of C–C glycosidic bonds - Wei, Bin; Wang, Ya-Kun; Qiu, Wen-Hui; Wang, Si-Jia; Wu, Yue-Hong; Xu, Xue-Wei; Wang, Hong (Applied microbiology and biotechnology, 2020)
C-Glycosides, a special type of glycoside, are frequently distributed in many kinds of medicinal plants, such as puerarin and mangiferin, showing various and significant bioactivities. C-Glycosides are usually characterized by the C–C bond that forms between the anomeric carbon of sugar moieties and the carbon atom of aglycon, which is usually resistant against acidic hydrolysis and enzymatic treatments. Interestingly, C-glycosides could be cleaved by several intestinal bacteria, but whether the enzymatic cleavage of C–C glycosidic bond is reduction or hydrolysis has been controversial; furthermore, whether existence of a “C-glycosidase” directly catalyzing the cleavage is not clear. Here we review research advances about the discovery and mechanism of intestinal bacteria in enzymatic cleavage of C–C glycosidic bond with an emphasis on the identification of enzymes manipulation the deglycosylation. Finally, we give a brief conclusion about the mechanism of C-glycoside deglycosylation and perspectives for future study in this field.